Multi-omics analyses reveal interactions between the skin microbiota and skin metabolites in atopic dermatitis - Huang, Kaikai; Li, Fang; Liu, Yingyao; Liang, Baoying; Qu, Pinghua; Yang, Linlin; Han, Shanshan; Li, Wenjun; Mo, Xiumei; Dong, Lei; Lin, Ying (Frontiers in Microbiology, 2024)
Introduction: Atopic dermatitis (AD) is one of the most common inflammatory skin diseases.Skin microecological imbalance is an important factor in the pathogenesis of AD, but the underlying mechanism of its interaction with humans remains unclear. Methods: 16S rRNA gene sequencing was conducted to reveal the skin microbiota dynamics.Changes in skin metabolites were tracked by LC-MS metabolomics. We then explored the potential mechanism of interaction by analyzing the correlation between skin bacterial communities and metabolites in corresponding skin-associated samples. Results: After quality control, samples from 18 AD patients and 18 healthy volunteers (HVs) were subjected to 16S rRNA gene sequencing and LC-MS metabolomics. AD patients had dysbiosis of the skin bacterial community with decreased species richness and evenness. The relative abundance of the genus Staphylococcus increased significantly in AD, while the abundances of the genera Propionibacterium and Brevundimonas decreased significantly. The relative abundance of the genera Staphylococcus in healthy females was significantly higher than those in healthy males, while it showed no difference in AD patients with or without lesions. The effects of AD status, sex and the presence or absence of rashes on the number of differentially abundant metabolites per capita were successively reduced. Multiple metabolites involved in purine metabolism and phenylalanine metabolism pathways (such as xanthosine/xanthine and L-phenylalanine/trans-cinnamate) were increased in AD patients. These trends were much more obvious between female AD patients and female HVs. Spearman correlation analysis revealed that the genus Staphylococcus was positively correlated with various compounds involved in phenylalanine metabolism and purine metabolic pathways. The genera Brevundimonas and Lactobacillus were negatively correlated with various compounds involved in purine metabolism, phenylalanine metabolism and sphingolipid signaling pathways. Discussion: We suggest that purine metabolism and phenylalanine metabolism pathway disorders may play a certain role in the pathogenic mechanism of Staphylococcus aureus in AD. We also found that females are more likely to be colonized by the genus Staphylococcus than males.Differentially abundant metabolites involved in purine metabolism and phenylalanine metabolism pathways were more obvious in female. However, we should notice that the metabolites we detected do not necessarily derived from microbes, they may also origin from the host.